2008
DOI: 10.1038/sj.bjp.0707602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KP‐496, a novel dual antagonist at the cysteinyl leukotriene receptor 1 and the thromboxane A2 receptor, on airway obstruction in guinea pigs

Abstract: Background and purpose: KP-496 is a novel dual antagonist for cysteinyl leukotriene receptor 1 (CysLT 1 ) and thromboxane A 2 (TXA 2 ) receptor (TP). The aim of this study was to evaluate the pharmacological profile of inhaled KP-496 and its effects on airway obstruction. Experimental approach: Antagonist activities of inhaled KP-496 were investigated using bronchoconstriction induced in guinea pigs by LTD 4 or U46619, a stable TXA 2 mimetic. Guinea pigs sensitized with injections of ovalbumin were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Except for IAR, these results are consistent with our previous report [24] . Since IAR has been considered a form of bronchoconstriction caused by histamine and lipid mediators such as cysLTs and TXA 2 , the discrepancy in findings between this and our previous report [24] about IAR might have mainly resulted from the fact that the animals were treated with or without H 1 antagonist before OA provocation. This finding is consistent with the results observed for RS-601 [22] .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Except for IAR, these results are consistent with our previous report [24] . Since IAR has been considered a form of bronchoconstriction caused by histamine and lipid mediators such as cysLTs and TXA 2 , the discrepancy in findings between this and our previous report [24] about IAR might have mainly resulted from the fact that the animals were treated with or without H 1 antagonist before OA provocation. This finding is consistent with the results observed for RS-601 [22] .…”
Section: Discussionsupporting
confidence: 83%
“…The antagonistic activities of KP-496 for both LTD 4 and TXA 2 are comparable to the cysLT receptor antagonists and TP antagonist already launched [23] . Furthermore, our previous study [24] demonstrated that inhaled KP-496 significantly inhibited antigen-induced bronchoconstriction, while sufficient doses of montelukast and seratrodast did not inhibit it. That study also demonstrated that inhaled KP-496 inhibited the immediate asthmatic response (IAR), late asthmatic response (LAR) and AHR, though no studies have presented findings concerning the anti-inflammatory effects of KP-496.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TXA 2 synthase inhibitors and TP receptor antagonists have been developed as anti-asthma drugs, and demonstrated to improve TP receptor-induced airflow limitation and bronchial hyperresponsiveness (Hanson et al, 2005;Ishimura et al, 2008;McKenniff et al, 1991). However, the signaling pathway responsible for modulation of TP receptor mediated airway hyperresponsiveness to TXA 2 is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, some specific inhibitors, notably cysteinyl leukotriene antagonists, have had promising clinical effects. Moreover, a study that used sensitised guinea-pigs reported that the use of dual antagonists that target cysteinyl leukotriene receptor 1 and thromboxane α -2 receptors had significant effects on airway obstruction in this animal model, suggesting that such an approach may prove beneficial in asthma treatment [6] .…”
Section: Mediator Inhibitorsmentioning
confidence: 97%